Female choise for male drumming characteristics in the wolf spider Hygrolycosa rubrofasciata - Parri, Silja (1999)
Female choice for male acoustic signalling and consequences of female selective mating behaviour were studied in the wolf spider Hygrolycosa rubrofasciata. Males of this species produce audible drumming signals that they use to attract females. These drumming sounds are audible also to human ear. When ready for mating females respond to these drummings by producing vibrations with their body. Drumming characteristics, such as drumming rate, vary between males. In this study I investigated the importance of several characteristics of the drumming signal on female choice. Females were found to prefer male signals of higher repetition rate and of greater length. Pulse rate of the signals did not affect female response behaviour. Repeatability and between male variation of the signal characteristics were used to categorise the signal traits into static and dynamic traits. Signal length was found to fulfil criteria of a trait that females could use to discriminate between males of different quality. Signal repetition rate has been found to indicate male phenotypic quality also in earlier studies. The possible consequences and benefits of female selective behaviour were studied in a selection experiment by mating females with males of either high or low drumming rate. Offspring survival and growth were compared between these two male categories. The offspring of the males with higher drumming rate were found to survive slightly better than the offspring of the lower drumming rate males. The results indicate that females of H. rubrofasciata might gain slight genetic, indirect benefits through their choice behaviour.